Temporal Expression Patterns of Genes Related to Sex Steroid Action in Sexually Dimorphic Nuclei During Puberty - Kanaya, Moeko; Morishita, Masahiro; Tsukahara, Shinji (Frontiers in Endocrinology, 2018)
Sex steroids play a major role in sexually dimorphic brain development during not only the perinatal period but also the pubertal period. We previously showed that, in male mice, the estrogen receptor-α (Esr1) and aromatase (Cyp19a1) genes are essential to the sexually dimorphic formation of the anteroventral periventricular nucleus (AVPV) and the principal nucleus of the bed nucleus of the stria terminalis (BNSTp), but the estrogen receptor-β (Esr2) gene is not necessary. We also showed that the androgen receptor (Ar) gene is essential to the sexually dimorphic formation of the BNSTp. These genes are expressed in the AVPV and BNSTp of perinatal mice. However, it remains unknown whether these genes are expressed in the AVPV and BNSTp during puberty, and whether the expression, if any, differs by sex, age and brain-region. Here, we dissected the AVPV and BNSTp from Nissl-stained brain sections of male and female mice on postnatal day (PD) 20 (prepuberty), PD30 (puberty onset in females), PD40 (puberty onset in males) and PD60 (young adult) using a laser microdissection system. We then examined the mRNA levels of Esr1, Esr2, Cyp19a1 and Ar in these brain regions. In the AVPV, Esr1 mRNA level was greater in females than males during PD20–60. Esr2 and Ar mRNA expression did not differ between sexes. Ar mRNA expression was higher at PD30 than PD20. Cyp19a1 mRNA was not detected in the AVPV at PD20–60. In the BNSTp, Esr1 and Esr2 mRNA levels were higher in females than in males during PD20–60, although the mRNA levels of Cyp19a1 and Ar did not differ between sexes. Additionally, we revealed that orchiectomy at PD20 induced a failure of normal formation of the male BNSTp and testosterone replacement in the prepubertal period rescued the effect of orchiectomy at PD20. Taken together, it is suggested that pubertal testosterone transported to the AVPV is not converted to estradiol there and dose not act via ESR1 and ESR2. In contrast, the formation of the male BNSTp may be affected by testicular testosterone during puberty via AR and/or via ESR1 after conversion to estradiol by CYP19A1.